1999
DOI: 10.1091/mbc.10.11.3971
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Yeast mRNAs as “Nonsense Containing” Leads to Both Inhibition of mRNA Translation and mRNA Degradation: Implications for the Control of mRNA Decapping

Abstract: A critical step in the degradation of many eukaryotic mRNAs is a decapping reaction that exposes the transcript to 5' to 3' exonucleolytic degradation. The dual role of the cap structure as a target of mRNA degradation and as the site of assembly of translation initiation factors has led to the hypothesis that the rate of decapping would be specified by the status of the cap binding complex. This model makes the prediction that signals that promote mRNA decapping should also alter translation. To test this hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 28 publications
(35 reference statements)
7
84
2
Order By: Relevance
“…The fact that our dual-reporter construct fails to report any effect of the UPF deletions tends to support the conclusion that the effect measured by Cui et al+ (1996) and Ruiz-Echevarria et al+ (1998) results from an increase in translation initiation rather than an increase in frameshifting+ Although Ruiz-Echevarria et al+ (1998) emphasize the threefold increase in expression of their Ϫ1 frameshift reporter caused by a ⌬upf3 mutation, they actually found that both ⌬upf1 and ⌬upf2 also caused an almost twofold increase in expression+ The effect noted by Muhlrad and Parker (1999) can explain these results+ At a minimum the conclusion that the surveillance complex regulates programmed Ϫ1 frameshifting must be considered suspect and attempts must be made to clearly show that the effect observed is a direct result of a change in frameshift efficiency+ The experiments of Cui et al+ (1996) and Ruiz-Echevarria et al+ (1998) do not directly address this point, as they contain no direct test of the effect of the upf mutations on translation initiation+…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The fact that our dual-reporter construct fails to report any effect of the UPF deletions tends to support the conclusion that the effect measured by Cui et al+ (1996) and Ruiz-Echevarria et al+ (1998) results from an increase in translation initiation rather than an increase in frameshifting+ Although Ruiz-Echevarria et al+ (1998) emphasize the threefold increase in expression of their Ϫ1 frameshift reporter caused by a ⌬upf3 mutation, they actually found that both ⌬upf1 and ⌬upf2 also caused an almost twofold increase in expression+ The effect noted by Muhlrad and Parker (1999) can explain these results+ At a minimum the conclusion that the surveillance complex regulates programmed Ϫ1 frameshifting must be considered suspect and attempts must be made to clearly show that the effect observed is a direct result of a change in frameshift efficiency+ The experiments of Cui et al+ (1996) and Ruiz-Echevarria et al+ (1998) do not directly address this point, as they contain no direct test of the effect of the upf mutations on translation initiation+…”
Section: Discussionmentioning
confidence: 75%
“…Wild-type strain HFY1200 and the congenic HFY870 (⌬upf1), HFY1300 (⌬upf2), and HFY863 (⌬upf3 ) strains were transformed with either pACTy, pACTTy, pAC1789 (HIV-1), pACLA (yeast L-A virus), or pAC1790+ Frameshifting efficiency is expressed as in Figure 2+ eRF has the opposite effect, reducing nonsense readthrough about twofold at each of the termination codons when they are present in an inefficiently recognized context+ These data are consistent with the data reported previously by Stansfield et al+ (1995)+ As expected, a [PSI ϩ ] strain also shows an increase in frameshifting at slippery-stop sites, programmed sites in which a codon particularly prone to allowing ϩ1 slippage by peptidyl-tRNA is immediately followed by a poorly recognized termination codon+ The effect was approximately five-to eightfold for two of the slipperystop constructions tested+ This is consistent with the idea that slow recognition of the termination codon allows ϩ1 slippage of the peptidyl-tRNA+ Indeed, UAA-C (FSt2) and UGA-C (FSt3) are inefficient for termination (Bonetti et al+, 1995), and are also highly sensitive to a PSI ϩ context+ Conversely, the UAA-G (FSt1) is more efficient for termination (Bonetti et al+, 1995) and is not sensitive to a PSI ϩ context+ The surveillance complex also appears to regulate termination+ Each of the ⌬upf mutations caused an increase in programmed termination readthrough, though the effects were small and variable+ Weak readthrough of an efficient UAA termination codon was stimulated approximately twofold by each of the ⌬upf mutations+ The ⌬upf mutations had no effect or marginal effects on the stronger readthrough at less efficient terminators+ This suggested that perturbation of the surveillance complex could have an effect on readthrough, but that its importance diminishes as the efficiency of eRF at a termination codon decreased+ This difference might suggest that the effect of the surveillance complex on termination is distinct from the effect of sequence context on eRF activity+ Where the sequence context causes eRF to have high intrinsic activity, a poor surveillance complex can lengthen pausing to stimulate readthrough, but as intrinsic activity is reduced, the ability of the UPF mutations to stimulate pausing further is reduced or lost+ More surprisingly, the UPF deletions had no effect on programmed Ϫ1 frameshifting+ These data directly contradict conclusions drawn by Cui et al+ (1996) and Ruiz-Echevarria et al+ (1998)+ They found evidence that mutations affecting the surveillance complex increased the efficiency of programmed Ϫ1 frameshifting+ For example, Ruiz-Echevarria et al+ (1998) showed an approximately twofold increase in relative expression of reporter constructs that required programmed Ϫ1 frameshifting+ Recent data from Muhlrad and Parker (1999) have shown that a ⌬upf mutation causes a two-to threefold increase in the rate of translational initiation on mRNAs normally subject to nonsense mediated decay (NMD)+ The lacZ single-reporter system used in the Cui et al+ (1996) and Ruiz-Echevarria et al+ (1998) experiments determines frameshift efficiency by comparing the expression of a reporter gene requiring frameshifting for expression of the lacZ product, b-galactosidase, to that of a reporter in which its expression does not require frameshifting+ It appears that the presence of a programmed frameshift site in the reporter makes the mRNA subject to NMD, whereas the reporter lacking such a site is not+ After adjusting for differences in mRNA stability, there appeared to be an excess increase in protein expression from the frameshift-reporter construct, FIGURE 6. Wild-type st...…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…One major effect is to specifically stabilize such mRNAs (29). Upf1p may also specifically alter translation termination or translation initiation on these mRNAs (24,(30)(31)(32)(33). The net effect of upf1⌬ is a suppression of the phenotype of premature stop codons.…”
Section: [Psi ؉ ] and Premature Stop Codonsmentioning
confidence: 99%
“…The complexity of the nonsense-mediated decay (NMD) system makes it difficult to study by comparing the expression of various single reporter constructs+ The known effects of the NMD genes include a reduction both in mRNA stability (reviewed by Czaplinski et al+, 1999) and in the efficiency of translational initiation (Muhlrad & Parker, 1999) of nonsense-containing plasmids as well as an apparent increase in the efficiency of translational termination as evidenced by increased readthrough of nonsense mutations (Bidou et al+, 2000;Maderazo et al+, 2000)+ The single reporter system can not distinguish among these effects and inference is required to determine which mechanism underlies any observed phenotypic effect on gene expression+ It is particularly problematic to differentiate the effects of translation initiation accuracy from putative effects on translational frameshifting+ The dual reporter system used in our work isolates the effect of translational frameshifting from effects on mRNA stability, initiation or termination+ Much is made by Dinman et al+ of the relative effects of various mutations, yet it remains unclear whether these are fundamental differences or simply differences in phenotypic strength of the various mutations+…”
mentioning
confidence: 99%